Speculation on the pathophysiology of musculoskeletal injury with COVID-19 infection - Veronesi, Francesca; Contartese, Deyanira; Martini, Lucia; Visani, Andrea; Fini, Milena (Frontiers in Medicine, 2022)
Coronavirus disease 2019 (COVID-19) primarily affects the respiratory tract, but also many other organs and tissues, leading to different pathological pictures, such as those of the musculoskeletal tissues. The present study should be considered as a speculation on the relationship between COVID-19 infection and some frequent musculoskeletal pathologies, in particular sarcopenia, bone loss/osteoporosis (OP) and fracture risk and osteoarthritis (OA), to hypothesize how the virus acts on these pathologies and consequently on the tissue regeneration/healing potential. The study focuses in particular on the modalities of interaction of COVID-19 with Angiotensin-Converting Enzyme 2 (ACE2) and on the “cytokine storm”. Knowing the effects of COVID-19 on musculoskeletal tissues could be important also to understand if tissue regenerative/reparative capacity is compromised, especially in elderly and frail patients. We speculate that ACE2 and serine proteases together with an intense inflammation, immobilization and malnutrition could be the responsible for muscle weakness, altered bone remodeling, increase in bone fracture risk and inflammatory joint pathologies. Future preclinical and clinical studies may focus on the regenerative/reparative properties of the musculoskeletal tissues after COVID-19 infection, towards a personalized treatment usually based on scaffolds, cells, and growth factors.